Antibacterial Mechanism of The Ehyl Acetate Extracts From Naked Oat Again Bacillus subtilis - Li-Huan Yuan; Qing-Ping Hu; Jian-Guo Xu (Aceh International Journal of Science and Technology, 2015)
The antibacterial mechanism of the ethyl acetate extracts from naked oat against Bacillus subtilis were studied in this paper based on assays such as cell wall alkaline phosphatase (AKP), permeability and integrity of cell membrane as well as electron microscopy observations. The results showed that the ethyl acetate extracts had significant effects on AKP, permeability and integrity of cell membrane. We concluded that the mechanism of action of the ethyl acetate extracts against B. subtilis might be described as:Acting on cell wall and membrane, resulting in disruption, cell lysis, and the leakage of intracellular constituents according to the results of AKP, the leakage of electrolytes, the losses of contents (proteins, reducing sugars and 260 nm absorbing materials) assays and electron microscopy observations. Overall, the results clearly indicated that the ethyl acetate extracts from naked oat was potential to control the contamination of foods caused by bacterial diseases